IMPROVING CRITICAL THINKING ABILITY THROUGH MAKE A MATCH MODEL ASSISTED BY PUZZLE MEDIA AT ELEMENTARY SCHOOLS - Ainun Fisabilillah Dina W. N; Ika Ari Pratiwi; Erik Aditia Ismaya (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to improve students’ critical thinking skills through make a match model assisted by puzzle media for elementary school students in the even semester of the academic year 2019/ 2020. This research was a Classroom Action Research (CAR) conducted in 2 cycles by using make a match as a learning method and puzzle as a learning medium. The subjects of this study were 26 students at grade V SD 3 Adiwarno, which consisted of 14 male students and 12 female students. The research data were collected by using the learning outcome test in the form of description question and non-test technique (interviews, observation, and documntation). The data from the test were analyzed descriptively and quantitatively. At the precycle stage consisting of PPKn and Social Science, the result of critical thinking test obtained an average of classical learning completeness of 1846 with a percentage of 44% (fairly good category). Then, the result of classical learning completeness obtained in cycle I was 2025 with a percentage of 73% in good category. Moreover, the result of classical learning completeness in cycle II was 2125 with a percentage of 85% in very good category. Thus, it could be concluded that make a match model assisted by puzzle media improved stuednts’ critical thinking skills.